The Relationship Between the Relevance of Learning Materials and the Learning Interest of Students at MDA Al-Ikhlas in Lembah Gumanti District - Widia Nanda Putri; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This study was carried out based on the observation that students at Madrasah Diniyah Awaliyah (MDA) Al-Ikhlas tend to show low engagement in learning activities, which is assumed to be related to the mismatch between the learning materials and their actual needs. The research aimed to explore the appropriateness of the learning materials, examine students’ level of learning interest, and analyze the relationship between these two aspects using a quantitative correlational approach. From a total population of 45 students, 25 were selected as respondents through simple random sampling, with data collected using questionnaires and analyzed through percentage techniques and Spearman Rank Order correlation. The findings revealed that both the relevance of the learning materials and students’ learning interest were still in the low category, and a significant relationship was identified between the two variables, indicating that better alignment of learning materials with students’ needs and real-life experiences can help increase their participation and engagement in the learning process.